PEMBERANTASAN TINDAK PIDANA KORUPSI DAN DIMENSI SISTEMATIK HUKUM KHUSUS - Nopsianus Max Damping (to-ra, 2018)
Abstract The legal politics of eradicating corruption in Indonesia has long been applied. This can be traced through a track record that begins with enforcement corruption eradication regulations around 1950, even then still in a limited scope, but at least in it has begun awareness arises about the importance of efforts to eradicate corruption. The rules on combating corruption rst appeared through regulations Ruler of War from Army Chief of Staff on April 16, 1950. No.Prt / Peperpu / 013/1958, and from the Navy Chief of Staff on April 17 1958. No.Prt / Z.I / 17. June 9, 1960. Second rule from the authorities this war, was later declared declared a Government Regulation In lieu of Law No. 24 Know 1960 about "Investigations, Prosecution, Corruption Investigation. Then there was reform welcomed by the community, and all components of the nation, to encourage a thorough renewal in the legal eld, and the government immediately undertook Amendments to a number of laws and regulations - especially regulations who took part in KKN, and one of them was the Law concerning Eradication of Corruption, Law No. 31 of 1999 concerning Eradication of Corruption Crime. Keyword: corruption crime; eradicating corruption; legal politics; KKN.